Functionalized aramid nanofiber as well as preparation method and application thereof

Functional aramid nanofibers were prepared through top-down peeling activation and Hoffman alkylation reaction, which solved the defects of the application of unfunctionalized fibers and the modification methods in the prior art, and achieved efficient and gentle nanofiber preparation and multifunctional applications.

CN119593197AActive Publication Date: 2025-03-11SUZHOU INST OF NANO TECH & NANO BIONICS CHINESE ACEDEMY OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411917084.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-11
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

In the existing preparation technology of aramid nanofibers, unfunctionalized fibers limit their application range, and existing modification methods have high energy consumption or damage to the fiber structure.

Method used

Functional aramid nanofibers were prepared by a top-down method through peeling activation reaction and Hoffman alkylation reaction. A large number of functional functional groups were grafted on the surface of the nanofibers, ensuring the mechanical properties and structural integrity of the fibers.

Benefits of technology

The efficient preparation of functional aramid nanofibers is achieved, and the mechanical properties and structure of the nanofibers are kept intact, with multiple functional application possibilities, mild reaction conditions, simple equipment, and the potential for rapid production expansion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119593197A_ABST
    Figure CN119593197A_ABST
Patent Text Reader

Abstract

The invention discloses a functionalized aramid nanofiber as well as a preparation method and application thereof. The preparation method comprises the following steps: mixing an organic solvent, a strong base, aramid fibers and a catalyst, carrying out a stripping activation reaction, and then adding a modification reagent to carry out a Hofmann alkylation reaction so as to prepare the functionalized aramid nanofibers. Aramid fibers are stripped into aramid nanofibers by adopting a method from top to bottom, then a modification reaction reagent is added, the functional aramid nanofibers are prepared through a rapid Hofmann alkylation reaction, and molecular chains in the nanofibers are aramid molecular chains, so that the crystal structure of the aramid fibers is not damaged, and the performance of the functional aramid nanofibers is improved. The mechanical property of the nanofiber is ensured; the surface of the prepared nanofiber is grafted with a large number of functional groups, and the grafting number is larger than that of a polymerization method; the method is mild in reaction process, controllable in reaction degree, good and perfect in nanofiber morphology and designable in functional group composition, and has functional application possibilities in multiple aspects of biological medicine, environment, energy and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an aramid nanofiber, in particular to a functionalized aramid nanofiber and a preparation method and application thereof, belonging to the technical field of new materials. Background Art

[0002] Aramid nanofibers are a new type of polymer nanofibers with excellent performance. Aramid nanofibers have high crystallinity and high internal rotation potential of the structure, which endows para-aramid fibers with high strength, high modulus, acid and alkali resistance, high temperature resistance and other properties. They can be efficiently compounded with polymer matrices through physical / chemical / self-assembly and other effects, becoming a "reinforcement building block" with great application potential in the field of composite reinforcement. The existing preparation technologies of aramid nanofibers are mainly alkali stripping and polymerization induced assembly. The aramid nanofibers obtained by these two methods are unfunctionalized fibers, which limits their application range, so further modification is needed.

[0003] The surface modification of aramid nanofibers can be divided into two methods: physical and chemical. In terms of physical modification, the surface of aramid nanofibers is modified mainly by plasma treatment, surface coating technology, ultraviolet radiation, gamma-ray radiation, and ultrasonic treatment. The purpose of these methods is to generate free radical active points on the fiber surface, thereby improving the functionality of the fiber surface in order to achieve better compatibility with composite materials. For example, plasma treatment can introduce oxygen-containing functional groups on the surface of aramid nanofibers. After subsequent treatment, the breaking of chemical bonds leads to an increase in the roughness of the fiber surface, thereby enhancing the interfacial shear force between the fiber and the matrix. Similarly, surface coating technology, ultraviolet radiation, gamma-ray radiation, and ultrasonic treatment methods all form active centers on the fiber surface through their own unique mechanisms, promote the introduction of polar groups, and thus improve the surface wettability and roughness of aramid nanofibers. These modification measures help to reduce problems such as stress defects caused by poor bonding between aramid nanofibers and composite materials.

[0004] Chemical modification technology has significantly improved the modification effect of aramid nanofibers. By introducing abundant active groups on the fiber surface, its surface activity is enhanced. This technology mainly covers two methods: surface etching and surface grafting. During the surface etching process, the fiber is treated with acyl chlorides and acid-base compounds, resulting in the hydrolysis of the amide bonds on the fiber surface, thereby enhancing the chemical activity and further enhancing the interaction between the fiber and the composite material interface. As the mainstream technology for modifying aramid nanofibers, the surface grafting method is mainly achieved by grafting polar groups or active groups that can undergo secondary reactions on the fiber surface. According to the different positions of the grafted functional groups, it can be divided into benzene ring grafting and amide bond grafting. In aramid nanofibers, the ortho-para hydrogen atoms on the benzene ring connected to the amino group have high reactivity and can undergo substitution reactions with electrophilic substituents, such as grafting -NH2 and -SO3H groups to the benzene ring through nitration reduction reaction and sulfonation reaction, respectively, to achieve further grafting of active groups. Although amide bonds can also be grafted, their nitration reduction and sulfonation reaction activities are low, resulting in unsatisfactory modification effects. The use of anhydrous and oxide-free metallization reaction technology can efficiently graft on the amide bond, and the surface activity can be improved by using alkali metals or alkaline earth metals and organic active substances (such as epoxy compounds) for surface modification. However, the reactants are highly active during the reaction, the reaction is dangerous, and accidents such as explosions are prone to occur.

[0005] In summary, the modification strategies for aramid nanofibers, whether physical or chemical, show different advantages and disadvantages. The physical modification method can maintain the original properties of the fiber to the greatest extent, and the damage to the fiber structure is relatively small. However, the physical modification process often requires more stringent environmental conditions, such as a vacuum environment or precise control of temperature, which leads to higher energy consumption. Relatively speaking, although chemical modification is easy to operate and has obvious modification effects, its process may cause a certain degree of damage to the internal structure of the fiber. Summary of the invention

[0006] The main purpose of the present invention is to provide a functionalized aramid nanofiber and a preparation method thereof, so as to overcome the deficiencies in the prior art.

[0007] Another object of the present invention is to provide applications of the functionalized aramid nanofibers.

[0008] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes: The embodiment of the present invention provides a method for preparing functionalized aramid nanofibers, which comprises: mixing an organic solvent, a strong base, aramid fibers and a catalyst, performing a stripping activation reaction, and then adding a modifying agent to perform a Hofmann alkylation reaction to obtain functionalized aramid nanofibers; Wherein, the molecular formula of the modifying reagent includes Ca H b O c X d S e M f , C a H b O c X d N e P f At least one of the following, X is a halogen element, M is a metal element, and a=1-20, b≥2, c≥0, d≥1, e≥0, in formula C a H b O c X d S e M f f, f ≥ 1, but in formula C a H b O c X d N e P f , f≥0.

[0009] The embodiment of the present invention also provides functionalized aramid nanofibers prepared by the above method.

[0010] The embodiments of the present invention also provide applications of the aforementioned functionalized aramid nanofibers in the fields of biomedicine, environment or energy.

[0011] Compared with the prior art, the beneficial effects of the present invention include: 1) The present invention adopts a top-down method to strip aramid fibers into aramid nanofibers and then add a modified reaction reagent. Through a rapid Hofmann alkylation reaction, the preparation of functional aramid nanofibers is achieved. The internal molecular chains of the nanofibers are aramid molecular chains, the crystalline structure of aramid is not destroyed, and the mechanical properties of the nanofibers are guaranteed; 2) The surface of the nanofibers prepared by the present invention is grafted with a large number of functional groups, and the number of grafted groups is greater than that of the polymerization method; the reaction process is mild, the reaction degree is controllable, the morphology of the nanofibers is good and perfect, and the composition of the functional groups can be designed, which has the possibility of functional application in many aspects such as biomedicine, environment, and energy; 3) The method of the present invention has high reaction efficiency, and eliminates the complex steps of drying, hydrolyzing, pickling, plasma treatment and the like of the aramid nanofibers required in the existing modification methods, thereby achieving one-pot preparation and modification of the nanofibers. The reaction is carried out at room temperature and atmospheric pressure, the reaction conditions are mild, the equipment is simple, and it has the potential for rapid expansion of production. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0013] Figure 1 is a flow chart for preparing a functionalized aramid nanofiber in a typical embodiment of the present invention; Figure 2 This is a photo of the modified aramid nanofiber slurry prepared in Example 1 of the present invention; Figure 3 This is a scanning electron microscope image of the organic metal salt-modified aramid nanofiber prepared in Example 1 of the present invention; Figure 4 This is a scanning electron microscope image of the organometallic salt-modified aramid nanofiber prepared in Example 2 of the present invention; Figure 5 This is an AFM photograph of the organometallic salt-modified aramid nanofiber prepared in Example 1 of the present invention; Figure 6 This is a scanning electron microscope image of the nitrogen-containing organic salt-modified aramid nanofiber prepared in Example 5 of the present invention. DETAILED DESCRIPTION

[0014] In view of the problems existing in the above-mentioned prior art, after long-term research and a large number of experiments, the inventors of this case proposed this technical solution, which mainly adopts a top-down approach to efficiently, safely and controllably prepare aramid nanofibers with functionalized functional groups on their surfaces through stripping-in-situ modification. This technology avoids the long polymerization and assembly process that requires fine control, and realizes the spontaneous termination of the reaction and the unimodal distribution of the nanofiber diameter through mechanism design, without damaging the aramid molecular chain, thereby ensuring the crystallinity and molecular weight of the nanofibers, so that they have higher strength and a longer aspect ratio.

[0015] The technical solution, its implementation process and principle will be further explained as follows.

[0016] The following terms require explanation: Aramid nanofiber: A fiber material with a nanometer-scale diameter composed of aramid molecules (PPTA, poly(p-phenylene terephthalamide)). Functionalized aramid nanofibers: aramid nanofibers that are modified or prepared by other methods and have certain functionality compared to aramid nanofibers.

[0017] As one aspect of the technical solution of the present invention, a method for preparing functionalized aramid nanofibers involves: mixing an organic solvent, a strong base, aramid fibers and a catalyst, performing a stripping activation reaction, and then adding a modifying agent to perform a Hofmann alkylation reaction to obtain functionalized aramid nanofibers.

[0018] In some embodiments, the molecular formula of the modifying reagent used in the present invention follows C a H b O c X d S e M f , wherein: C is carbon element, H is hydrogen element, O is oxygen element, X is halogen element (for example, it can be any one of F, Cl, Br, I, etc.), S is sulfur element, M is metal ion (for example, it can be any one of K, Na, Ca, Li, Mg, Zn, Fe, Sn, Cu, etc.), the range of a is 1 to 20, the range of b is greater than or equal to 2, the range of c is greater than or equal to 0, the range of d is greater than or equal to 1, the range of e is greater than or equal to 0, and the range of f is greater than or equal to 1.

[0019] In other embodiments, the molecular formula of the modifying agent used in the present invention can also follow C a H b O c X d N e P f , where: C is carbon, H is hydrogen, O is oxygen, X is a halogen (for example, any one of F, Cl, Br, I, etc.), N is nitrogen, P is phosphorus, a ranges from 1 to 20, b ranges from greater than or equal to 2, c is greater than or equal to 0, d ranges from greater than or equal to 1, e ranges from greater than or equal to 0, and f ranges from greater than or equal to 0.

[0020] The reaction principle of the present invention is that a strong base abstracts hydrogen to form a nitrogen anion, and then the nitrogen anion is grafted onto a functional group through an alkylation reaction. Different proportions of nitrogen anions can be formed on the surface of the aramid according to the ratio of the strong base to the aramid. At the same time, the amide bond on the aramid is a tertiary amine, so only one substitution functional group will be grafted.

[0021] In some embodiments, the mass ratio of the aramid fiber, organic solvent, strong base, catalyst and modifying agent is 1: 9-99: 0.2-5: 0.2-5: 0.01-50. In other words, with the mass of the aramid fiber as 1, the mass ratios of the remaining components are as follows: organic solvent 9-99, strong base 0.2-5, catalyst 0.2-5, modifying agent 0.01-50.

[0022] In some embodiments, the aramid fiber may include any one of para-aramid fiber, meta-aramid fiber, aramid III fiber (heterocyclic aramid), etc., or a combination of two or more thereof, but is not limited thereto.

[0023] In some embodiments, the organic solvent may include any one or a combination of two or more of dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, methanol, ethanol, water, etc., but is not limited thereto.

[0024] In some embodiments, the strong base includes any one of an organic base and an inorganic base.

[0025] In some preferred embodiments, the inorganic base may include any one or a combination of two of hydroxide, hydride, etc., but is not limited thereto.

[0026] In some more specific embodiments, the hydroxide may include any one or a combination of two or more of potassium hydroxide, sodium hydroxide, calcium hydroxide, etc., but is not limited thereto.

[0027] In some more specific embodiments, the hydride may include any one or a combination of two or more of potassium hydride, calcium hydride, sodium hydride, etc., but is not limited thereto.

[0028] In some preferred embodiments, the organic base may include any one or a combination of two or more organic bases having metal ions such as sodium tert-butoxide, potassium tert-butoxide, n-butyl lithium, potassium methoxide, etc., but is not limited thereto. The present invention adds a base content to stimulate different amounts of nitrogen anion sites, and grafts hydrophilic functional groups on the nitrogen anion sites by Hofmann alkylation reaction. The amount of grafting can be controlled by the amount of base added.

[0029] In some preferred embodiments, the catalyst may include any one or a combination of two or more of ethylene glycol, glycerol, formic acid, methanol, ethanol, water, etc., but is not limited thereto.

[0030] In some embodiments, the modifying agent is added by any one of dropwise addition, direct mixing, and the like.

[0031] In some embodiments, the preparation method specifically includes: mixing an organic solvent, a strong base, aramid fiber and a catalyst for 1 to 48 hours to perform a stripping activation reaction.

[0032] In some embodiments, the Hofmann alkylation reaction is carried out at a temperature of 20 to 120° C. and for a time of 0.5 to 48 h.

[0033] As one of the more specific embodiments, the present invention prepares water-based functionalized aramid nanofibers by a dynamic equilibrium stripping modification method, such as Figure 1 As shown, the specific implementation steps of the method are as follows: an organic solvent, a strong base, aramid fiber and a catalyst are mixed for 1 to 48 hours to perform a stripping activation reaction, and an initial reaction solution is obtained after the reaction is completed. A modifying agent is added to the initial reaction solution, and after adding the modifying agent, the reaction is stirred until the color of the reaction system solution does not change to obtain a reaction product, and the unreacted strong base and the modifying agent are filtered through a filter to obtain a cationic functionalized aramid nanofiber dispersion.

[0034] The functionalized aramid nanofiber preparation reaction process provided by the present invention is carried out in the wet phase throughout. The homogeneous reaction design eliminates the complicated steps of drying, hydrolyzing, pickling, plasma treating and the like required for the aramid nanofiber modification in the existing modification method, thereby achieving one-pot production and greatly improving the production efficiency.

[0035] In summary, the preparation method of the present invention adopts a molded polymer, and after stripping the nanofibers from top to bottom, a modified reaction reagent is added to obtain water-based nanofibers through a rapid Hofmann alkylation reaction. This technology avoids the long and finely controlled polymerization and assembly process, and realizes the spontaneous termination of the reaction and the unimodal distribution of the nanofiber diameter through mechanism design, and does not damage the aramid molecular chain, ensuring the crystallinity and molecular weight of the nanofibers, so that they have higher strength and a longer aspect ratio. At the same time, the reaction is carried out at room temperature and atmospheric pressure, the reaction conditions are mild, the equipment is simple, and there is the potential for rapid expansion.

[0036] Another aspect of an embodiment of the present invention further provides a functionalized aramid nanofiber prepared by the aforementioned preparation method, which has a plurality of functionalized functional groups on its surface, thus also bringing about differences in performance. In terms of performance, depending on the different functional groups, the nanofiber can achieve adsorption and affinity for different gases and liquids, luminescence under light stimulation, and a higher flame retardant effect.

[0037] Specifically, the internal molecular chains of the functionalized aramid nanofibers of the present invention are aramid molecular chains, so the crystalline structure of aramid is not destroyed and the mechanical properties of the nanofibers are guaranteed; a large number of functional groups are grafted onto the surface of the nanofibers, and the grafting amount is greater than that of the polymerization method.

[0038] The functionalized aramid nanofibers prepared by the present invention can be dispersed in different materials and have certain functionalization, and the functionalization is manifested in that it can adsorb specific substances or has properties such as luminescence and flame retardancy. This is caused by the functional groups corresponding to nitrogen, phosphorus or sulfur in the group, so that the materials obtained after the aramid nanofibers are composited with other materials have different properties and have good compatibility with the base material.

[0039] Another aspect of the embodiments of the present invention further provides the application of the aforementioned functionalized aramid nanofibers.

[0040] By means of the above technical scheme, the reaction process of the present invention is mild, the reaction degree is controllable, the nanofiber morphology is well-developed, the functional group composition can be designed, and it has the possibility of functional application in many aspects such as biomedicine, environment, and energy.

[0041] Furthermore, the method of the present invention has high reaction efficiency and eliminates the complex steps of drying, hydrolyzing, pickling, plasma treatment and the like of the aramid nanofibers required in the existing modification methods, thereby achieving one-pot preparation and modification of the nanofibers. The reaction is carried out at room temperature and atmospheric pressure, the reaction conditions are mild, the equipment is simple, and there is the potential for rapid expansion of production.

[0042] The whole process is described in detail below through several embodiments and drawings, but the protection scope of the present invention is not limited by these embodiments. At the same time, the embodiments only provide some conditions for achieving this purpose, but do not mean that these conditions must be met to achieve this purpose. All variations associated with or derived from the contents disclosed in the present invention are considered to be within the protection scope of the present invention.

[0043] Example 1 10g of para-aramid fiber was mixed with 10g of potassium hydroxide, 980g of dimethyl sulfoxide, and 10g of ethanol and stirred for 20h to dissolve. 50g of C2H4O2NaCl was added and stirred at room temperature (25°C) for 20h to obtain the reaction product. The excess unreacted salt was filtered out by a positive pressure filter to obtain the purified hydrophilic aramid nanofiber slurry. The obtained slurry is shown in the photo. Figure 2 The SEM images of the obtained organometallic salt modified aramid nanofibers are shown in Figure 3 As shown, the average diameter of the aramid nanofibers is 35 nm. The AFM images of the obtained organometallic salt-modified aramid nanofibers are shown in Figure 5 shown.

[0044] Example 2 30g of para-aramid fiber was mixed with 20g of potassium hydroxide, 980g of dimethyl sulfoxide, and 20g of methanol, and stirred for 20h to dissolve. 50g of C2H4O2NaCl was added and stirred at room temperature (25°C) for 30h to obtain the reaction product. The excess unreacted salt was filtered out by a positive pressure filter to obtain a purified hydrophilic aramid nanofiber slurry. The SEM photo of the obtained organometallic salt modified aramid nanofiber is shown in Figure 4 As shown, the average diameter of the nanofibers is 30 nm.

[0045] Example 3 Mix 10g of meta-aramid fiber with 10g of potassium hydride, 980g of dimethylformamide, and 10g of ethanol and stir to dissolve for 20h. Add 140g of C7H 17N2Br and then stirred at 40°C for 48h to obtain the reaction product, and the excess unreacted salt was filtered out by a positive pressure filter to obtain the purified CO2 adsorbed aramid nanofibers.

[0046] Example 4 10g of aramid III fiber was mixed with 30g of potassium tert-butoxide, 980g of dimethyl sulfoxide, and 10g of water and stirred for 40h to dissolve. 94g of C5H 14 NCl was added and stirred at 40° C. for 0.5 h to obtain a reaction product, and excess unreacted salts were filtered out using a positive pressure filter to obtain a purified aramid nanofiber slurry. The nanofiber has adsorption properties for acidic gases.

[0047] Example 5 40g of para-fiber was mixed with 30g of potassium methoxide, 900g of N-methylpyrrolidone, and 10g of ethanol and stirred for 40h to dissolve. 3g of C 15 The H8O2NCl2 was heated to 80℃ and stirred for 14h. The reaction product was separated by high-speed centrifugation to obtain a purified aramid nanofiber slurry. The nanofiber had a fluorescence excitation effect. The SEM image of the obtained nitrogen-containing organic salt modified aramid nanofiber is shown in Figure 2. Figure 6 As shown, the average diameter of the nanofibers is 60 nm.

[0048] Example 6 10g of para-aramid fiber was mixed with 10g of potassium hydroxide, 980g of dimethyl sulfoxide, and 10g of methanol and stirred for 20h to dissolve. 50g of C9H 15 O4PCl3 was added and stirred at room temperature (25°C) for 2 hours to obtain the reaction product. The excess unreacted salt was filtered out by a positive pressure filter to obtain a purified highly flame-retardant aramid nanofiber slurry. The oxygen index of the obtained aramid nanofiber reached 38%.

[0049] Example 7 10g of para-aramid fiber was mixed with 50g of potassium hydroxide, 90g of dimethyl sulfoxide, and 2g of ethanol, and stirred for 48h. After adding 0.1g of CH3OCl, it was stirred for 1h at room temperature (25°C) to obtain a reaction product. The excess unreacted salt was filtered out by a positive pressure filter to obtain a purified hydrophilic aramid nanofiber slurry. The average diameter of the obtained nanofibers was 800nm, and the fibers could be better dispersed in water.

[0050] Example 8 10g of para-aramid fiber was mixed with 10g of potassium hydroxide, 980g of dimethyl sulfoxide, and 10g of ethanol and stirred for 20h to dissolve. 50g of C 20 H 40 O2NaCl and then heated to 90°C and stirred for 48h to obtain a reaction product, and a positive pressure filter was used to filter excess unreacted salts to obtain a purified hydrophilic aramid nanofiber slurry.

[0051] Example 9 10 g of para-aramid fiber was mixed with 50 g of sodium hydride, 990 g of N-methylpyrrolidone and 2 g of propylene glycol and stirred to dissolve for 1 h. After adding 100 g of C2H6ClNaO4S, the temperature was raised to 120°C and stirred for 15 h to obtain a reaction product. The excess unreacted salt was filtered out using a positive pressure filter to obtain a purified hydrophilic aramid nanofiber slurry.

[0052] Example 10 10 g of para-aramid fiber was mixed with 20 g of n-butyl lithium, 980 g of N-methylpyrrolidone and 3 g of formic acid and stirred to dissolve for 24 h. After adding 500 g of C4H8O4ClCa, the mixture was stirred at 20°C for 48 h to obtain a reaction product. The excess unreacted salt was filtered out using a positive pressure filter to obtain a purified hydrophilic aramid nanofiber slurry.

[0053] Comparative Example 1 10 g of para-aramid fiber was mixed with 10 g of potassium hydroxide, 980 g of dimethyl sulfoxide, and 10 g of methanol, and stirred to dissolve for 20 hours. After adding 50 g of propyne bromide, the mixture was stirred at room temperature for 2 hours to obtain a reaction product. The obtained nanofiber had a diameter of 40 nm, and the obtained product did not show changes in affinity for gas, water, and organic reagents, stimulate luminescence, or change in flame retardant properties.

[0054] Comparative Example 2 10 g of para-aramid fiber was mixed with 10 g of potassium hydroxide, 980 g of dimethyl sulfoxide, and 10 g of methanol, and stirred to dissolve for 20 hours. After adding 20 g of 1-bromo-2-butyne, the mixture was stirred at room temperature for 2 hours to obtain a reaction product. The average diameter of the obtained nanofibers was 20 nm. The obtained product did not show changes in affinity for gas, water, and organic reagents, stimulate luminescence, or change in flame retardant properties.

[0055] In addition, the inventors of this case also conducted experiments with other raw materials and conditions listed in this specification in accordance with the aforementioned embodiments, and obtained relatively ideal results.

[0056] The various aspects, embodiments, features and examples of the present invention should be considered to be illustrative in all aspects and are not intended to limit the present invention. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0057] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made and that substantial equivalents may be substituted for elements of the described embodiments without departing from the spirit and scope of the present invention. In addition, many modifications may be made to adapt a particular situation or material to the teachings of the present invention without departing from the scope of the present invention.

Claims

1. A method for preparing functionalized aramid nanofibers, characterized in that: include: An organic solvent, a strong base, aramid fibers and a catalyst are mixed to perform a stripping activation reaction, and then a modifying agent is added to perform a Hofmann alkylation reaction to obtain functionalized aramid nanofibers; Wherein, the molecular formula of the modifying reagent includes C a H b O c X d S e M f , C a H b O c X d N e P f At least one of the following, X is a halogen element, M is a metal element, and a=1-20, b≥2, c≥0, d≥1, e≥0, in formula C a H b O c X d S e M f f, f≥1, but in formula C a H b O c X d N e P f , f≥0.

2. The preparation method according to claim 1, characterized in that: In formula C a H b O c X d S e M f In the above, X includes any one of F, Cl, Br, and I; and / or M includes any one of K, Na, Ca, Li, Mg, Zn, Fe, Sn, and Cu.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the aramid fiber, the organic solvent, the strong base, the catalyst and the modifying agent is 1:9-99:0.2-5:0.2-5:0.01-50.

4. The preparation method according to claim 1, characterized in that: The aramid fiber includes any one of para-aramid fiber, meta-aramid fiber, and aramid III fiber, or a combination of two or more thereof; And / or, the organic solvent includes any one or a combination of two or more of dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, methanol, ethanol, and water.

5. The preparation method according to claim 1, characterized in that: The strong base includes any one of an organic base and an inorganic base; Preferably, the inorganic base includes any one of hydroxide and hydride or a combination of two thereof; particularly preferably, the hydroxide includes any one of potassium hydroxide, sodium hydroxide and calcium hydroxide or a combination of two or more thereof; particularly preferably, the hydride includes any one of potassium hydride, calcium hydride and sodium hydride or a combination of two or more thereof; Preferably, the organic base includes any one or a combination of two or more of sodium tert-butoxide, potassium tert-butoxide, n-butyl lithium, and potassium methoxide; And / or, the catalyst includes any one of ethylene glycol, propylene glycol, formic acid, methanol, ethanol, and water, or a combination of two or more thereof.

6. The preparation method according to claim 1, characterized in that: The adding method of the modifying agent includes any one of dropwise addition and direct mixing.

7. The preparation method according to claim 1, characterized in that: include: The organic solvent, strong base, aramid fiber and catalyst are mixed for 1 to 48 hours to perform a stripping activation reaction.

8. The preparation method according to claim 1, characterized in that: The temperature of the Hofmann alkylation reaction is 20-120° C. and the time is 0.5-48 h.

9. The functionalized aramid nanofiber prepared by the preparation method according to any one of claims 1 to 8, wherein the surface of the functionalized aramid nanofiber has a plurality of functional groups.

10. Use of the functionalized aramid nanofiber according to claim 9 in the fields of biomedicine, environment or energy.

Citation Information

Patent Citations

  • Polyimide resin composition, and (polyimide resin)-fiber composite material

    CN105392842A

  • Organic fibers and textile products

    US20040034941A1

  • Surface-modified aramid fiber and preparation method therefor

    US20210222358A1